Religion and Education in the Shadow of the European Court of Human Rights - Fokas, Effie (2019)
This article presents a symposium on the "indirect effects" of the European Court of Human Rights jurisprudence on the place of religion in the educational sphere. The symposium showcases empirical research providing critical insight into how the Court's decisions may influence related domestic debates, raise public consciousness, and change how social actors perceive their rights and articulate their right claims in the area of religion and education. The research underpinning this symposium represents a clear departure from existing scholarship in this domain: it examines the impact of the Court not from the top-down (Court impact on states and their legislative frameworks) but from grassroots level upwards, in seeking to understand whether, how and to what extent Court decisions influence grassroots level actors' conceptions of their rights in the domain of religion and education and their efforts to secure new rights vis-à-vis their states.